Apakah Sepsis Perlu Dilakukan CRRT - Suparno Suparno; Bowo Adiyanto (Jurnal Medika Nusantara, 2024)
Sepsis is a condition of systemic inflammation due to dysregulation of the immune system against infection which causes multiorgan failure. One of the most frequent complications of sepsis and has a high mortality rate is acute renal failure (AKI). Often, sepsis that has already occurred requires renal replacement therapy (RRT). The continuous renal replacement therapy (CRRT) technique is currently more widely used than other techniques, namely intermittent hemodialysis (IHD). IHD often causes hemodynamic problems and even causes cardiac arrest in patients who experience hemodynamic disorders in the ICU. Apart from being useful in AKI, CRRT is also useful in eliminating mediators in sepsis. This aims to reduce the severity of cytokine storms and pro-inflammatory endotoxins thereby improving patient outcomes. Several methods and devices such as high cut-off membranes, Oxiris®-AN69 membranes, CytoSorb® and HA380 cytokine hemoadsorption, polymyxin B endotoxin adsorption and plasmapheresis have been widely observed as ways to improve outcomes in septic patients. However, until now data regarding actual benefits is still controversial. This article reviews the benefits and standard operational procedures of RRT in sepsis patients.